Gangliosides for the treatment of diabetic peripheral neuropathy - Mallik,S; Kallis,C; Lunn,MPT; Smith,AG (Cochrane Database of Systematic Reviews, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the benefits and harms of treatment with gangliosides in diabetic peripheral neuropathy.